Can Central Asia be integrated as asean? - Iskakova, Zhainara; Sarsembayev, Marat; Kakenova, Zarina (Opción, 2018)
This article examines the role of the one of the most influential contemporary regional political and economic organization of the Association of Southeast Asian Nations (ASEAN) as an example for further integration of Central Asian countries: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. The role of security organizations in the context of integration also has been used. Based on the findings of this paper, Asian countries have sufficient resources and motivation to prepare for sustainable continental convergence by establishing a meaningful relationship between the experiences of different regionalism in Asia.